2006
DOI: 10.1359/jbmr.060726
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte–Deficient Mice Lose Trabecular Bone Mass With Ovariectomy

Abstract: We examined OVX-induced bone loss in three TLD mouse models. In TLD mice, OVX caused trabecular bone loss equivalent to that of WT. In contrast, cortical bone loss with OVX was variable. We conclude that T lymphocytes do not influence OVX-induced trabecular bone loss. Introduction:We examined ovariectomy (OVX)-induced bone loss in three T lymphocyte-deficient (TLD) mouse models: nude mice, recombination activating gene 2-deficient (RAG2 KO) mice, and ⌻ cell receptor ␣ chain-deficient (TCR␣ KO) mice. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 55 publications
5
85
1
1
Order By: Relevance
“…An independent confirmation of the role of T cells was provided by Yamaza et al (26), who reported that ovx fails to induce bone loss in nude mice and WT mice in which T-cell activation was blocked by aspirin. By contrast, Lee et al (48) showed that nude mice are protected against the loss of cortical but not trabecular bone induced by ovx. In the same study, other strains of T-cell and T-and B-cell deficient mice were found to lose either trabecular or cortical bone after ovx (48).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An independent confirmation of the role of T cells was provided by Yamaza et al (26), who reported that ovx fails to induce bone loss in nude mice and WT mice in which T-cell activation was blocked by aspirin. By contrast, Lee et al (48) showed that nude mice are protected against the loss of cortical but not trabecular bone induced by ovx. In the same study, other strains of T-cell and T-and B-cell deficient mice were found to lose either trabecular or cortical bone after ovx (48).…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, Lee et al (48) showed that nude mice are protected against the loss of cortical but not trabecular bone induced by ovx. In the same study, other strains of T-cell and T-and B-cell deficient mice were found to lose either trabecular or cortical bone after ovx (48). The discrepancy between our reports (17,24,25,43,44) and that of Lee et al (48) is likely explained by differences in the experimental design, the lack of B cells in some models, and compensation mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…T lymphocytes are thought to be involved in the bone loss caused by ovariectomy in mice (15), although some studies have been unable to demonstrate a requirement for this cell type (50). The major mechanism is thought to be increased production of T cells that produce TNF␣ (51), with a possible additional contribution of RANKL produced by T cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 During estrogen deficiency the immune response is altered and, in particular, T cells become more active and able to produce inflammatory and pro-osteoclastogenic cytokines such as TNFa and RANKL. Despite some inverse reports, 34,35 the main body of literature firmly supports the essential role of activated T cells in regulating bone loss induced by estrogen deficiency, 5,[36][37][38] both in animal models and in humans.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%